Gorgeous Footwear / Wan Faizun Zaffan Hj. Abd. Hamid ... [et al.] - Hj. Abd. Hamid, Wan Faizun Zaffan; Ardi, Nordiana; Mohd Halimi, Nuruz Zuhriah; Lukman, Dina Kartini (Faculty of Art and Design, 2004)
Alhamdulillah thanks to Allah swt to Allah with his blessing and help we had succeded done a report of Business Planning to complete the course we are studying. As the completed of Business Planning,we has gained a lot of experiences on this kind of studies.Besides that,we can create a new relationships with the community and leam how a group of people can do something better when they are unite.